Boyle on Atheism - Boyle, Robert, 1627-1691 (Book collections on Project MUSE., 2005)
"With Boyle on Atheism, J.J. MacIntosh has culled the Boyle manuscripts held at the Royal Society Library in London and transcribed the portions that relate to atheism, arranging them in the order Boyle appears to have intended (as outlined in one of the pieces). Included are Boyle's views on the causes (and remedies) of atheism, the nature of God, various possible arguments for God's existence, the excellency of Christianity, and the character of atheists and the deficiencies to be found in their arguments."--Jacket